NILAI PERUSAHAAN DARI PERSPEKTIF GENDER DIVERSITY, CORPORATE SOCIAL RESPONSIBILITY DAN KINERJA KEUANGAN - Mefthahul Hidayat; Wira Ramashar; Zul Azmi (Jurnal Akuntansi Kompetif, 2026)
This study aims to analyze the influence of corporate social responsibility (CSR), financial performance, and gender diversity. The research subjects were manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange for the 2021–2024 period. Firm value was proxied using Tobin's Q, CSR was measured using the Corporate Social Responsibility Index (CSRI), financial performance was proxied by Return on Assets (ROA), and gender diversity was measured based on the presence of women on the board of directors or commissioners. This study employed a quantitative approach with a purposive sampling technique. Data were analyzed using multiple linear regression after first conducting classical assumption tests. The results showed that financial performance had a positive effect on firm value, while corporate social responsibility and gender diversity showed inconsistent effects on firm value. These findings support signaling theory, which states that financial and non-financial information provided by companies can serve as signals for investors in assessing the company's prospects.